Evaluasi Penggunaan Tepung (Batang+Daun) Tanaman Kenikir (Cosmos Caudatus Kunth) sebagai Feed Additive terhadap Kualitas Internal Telur Ryam Ras Petelur - Maria Selfiana Pasi (JAS, 2021)
The purpose of this study was to evaluate the effect of using cosmos caudatus Kunth flour (stem + leaves) on the internal quality of laying eggs. This research has been conducted in Bacem Village, Sutojayan District, Kab. Blitar. This study uses an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 6 replications. Treatment P0 = Basal feed + 0% flour (stem + leaves) cosmos caudatus Kunth, P1 = Basal feed + 0.25% flour (stem + leaves) cosmos caudatus Kunth, P2 = Basal feed + 0.50% flour (stem + leaves) cosmos caudatus Kunth, P3 = Basal feed + 0.75% flour (stem + leaves) cosmos caudatus Kunth. The parameters observed were the weight of the egg white, the proportion of egg white, the weight of the egg yolk, the proportion of the yolk and the score of the yolk color. The results showed that the administration of flour (stem + leaves) cosmos caudatus Kunth plant as a feed additive can provide a very significant effect (P <0.01) on the weight of egg white, and no significant effect (P> 0.05) on the proportion of egg white, weight egg yolk, proportion of egg yolk and egg yolk color score. The results of this study it can be concluded that the administration of flour (stem + leaves) cosmos caudatus Kunth as a feed additive can affect the quality of internal eggs.